Tropical Forages – an interactive selection tool. 2020 Report. - Burkart, Stefan; Urrea Benítez, José Luis (Bioversity International and the International Center for Tropical Agriculture, 2020)
In August 2020, the International Center for Tropical Agriculture (CIAT) and the International Livestock Research Institute (ILRI) released the second, revised edition of Tropical Forages: an interactive selection tool. Originally launched in 2005, the tool aims at promoting adoption of a large suite of grasses and legumes to be used as livestock feeds and for ecosystems services e.g. to help curb greenhouse gas emissions and reverse land degradation. Tropical Forages is available at www.tropicalforages.info. This report provides a brief overview on the tool, its development and release in 2020, user statistics, dissemination efforts and future maintenance and development needs.